Implementation of Total Quality Management (TQM) At Sri Kembang Village Elementary School Betung District - Nita, Vini Alpian; Lian, Bukman; Nugroho, Hery Setiyo (Raudhah Publisher, 2024)
This research aims to describe and analyze the implementation of Total Quality Management (TQM) in SDN 7 Betung and SDN 20 Betung, as well as to describe and analyze the obstacles and solutions faced in the implementation of TQM in the two schools. This qualitative research employed a case study approach. Data collection techniques involved observation, interviews, and documentation. The data analysis techniques utilized were domain analysis and thematic analysis. The research findings revealed that 1. The implementation of TQM in SDN 7 Betung and SDN 20 Betung is quite optimal. This is evident from the improvement in the quality of education in both schools. 2. The obstacles encountered in the implementation of TQM in SDN 7 Betung and SDN 20 Betung include a lack of understanding of the concept of quality management, insufficient training and mentoring for principals and teachers, and inadequate facilities and infrastructure. The potential solutions to address these obstacles involve providing training and mentoring for principals and teachers on the concept of quality management and furnishing adequate facilities and infrastructure.